Analisis Pengaruh Self Efficacy Terhadap Subjective Wellbeing Dimediasi Oleh Organizational Crisis Preparedness Pada UKM di Sumatera Barat - Ariliusra, Azzukhruf (Jurnal Ilmiah Ekotrans & Erudisi, 2023)
This study was conducted to determine the effect of learning behaviour from failure on subjective well-being through organizational crisis preparedness as a mediating variable. The method used in this study is quantitative, data collection with questionnaires, sampling was carried out by convenience sampling with a sample of 216 people but 200 questionnaires were returned. The data analysis technique used a structural equation model (SEM) with the help of SmartPLS. The results obtained from this study indicate a positive relationship between self-efficacy and subjective wellbeing and have a significant effect. The mediation analysis found that there was no mediation effect through organizational crisis preparedness on self-efficacy with subjective well-being.